2008
DOI: 10.4141/cjps07047
|View full text |Cite
|
Sign up to set email alerts
|

Use of a detached leaf screening method for segregating Colorado potato beetle (Leptinotarsa decemlineata Say) resistant Solanum hybrid lines

Abstract: S. 2008. Use of a detached leaf screening method for segregating Colorado potato beetle (Leptinotarsa decemlineata Say) resistant Solanum hybrid lines. Can. J. Plant Sci. 88: 633Á638. A diploid segregating population for resistance to Colorado potato beetle (CPB) was developed by crossing the resistant Mexican species Solanum pinnatisectum (S. pnt., 2n 02x024) with the susceptible S. cardiophyllum (S. cph., 2n 0 2x 024). A resistant hybrid plant from this cross was selected and backcrossed as a female to S. cp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…There are some methods, which can be used to test the CPB more easily. Laboratory-based methods, such measuring leaf consumption by adult CPB in petri dishes (Nandy et al 2008;Cooper et al 2009), suppression of larval survival and inhibition of larval growth on detached leaves (Lorenzen et al 2001;Cooper et al 2009) can be good methods for evaluation of CPB resistance in potato as long as they reflect the resistance expressed in the field. Several rearing methods for CPB have been established to support the lab-based evaluation method (Gelman et al 2001;Thorpe and Bennett 2003).…”
Section: Prospects Of Cpb Resistance Breedingmentioning
confidence: 99%
“…There are some methods, which can be used to test the CPB more easily. Laboratory-based methods, such measuring leaf consumption by adult CPB in petri dishes (Nandy et al 2008;Cooper et al 2009), suppression of larval survival and inhibition of larval growth on detached leaves (Lorenzen et al 2001;Cooper et al 2009) can be good methods for evaluation of CPB resistance in potato as long as they reflect the resistance expressed in the field. Several rearing methods for CPB have been established to support the lab-based evaluation method (Gelman et al 2001;Thorpe and Bennett 2003).…”
Section: Prospects Of Cpb Resistance Breedingmentioning
confidence: 99%
“…The genetics of resistance to the CPB in S. pinnatisectum was studied using a resistant 2n hybrid population with S. cardiophyllum (Chen et al 2004) and revealed that only two genes are responsible for resistance in S. pinnatisectum (Nandy et al 2008). Interspecific somatic hybrids between S. tuberosum and S. pinnatisectum were regenerated following electrofusion of mesophyll protoplasts (Thieme et al 1997;Chen et al 2008) and some of that material has been developed to the BC 4 stage (R. Thieme, pers.…”
Section: S Pinnatisectummentioning
confidence: 99%
“…Interspecific somatic hybrids between S. tuberosum and S. pinnatisectum were regenerated following electrofusion of mesophyll protoplasts (Thieme et al 1997;Chen et al 2008) and some of that material has been developed to the BC 4 stage (R. Thieme, pers. comm.…”
Section: S Pinnatisectummentioning
confidence: 99%
See 2 more Smart Citations